Impact of simulation training on pre-clinical and clinical practice: the example of Tallinn Health Care College - Jandra Ristikivi; Irma Nool; Kadri Kööp; Urve Kaasik Aaslav (Proceedings of the Estonian Academy of Sciences, 2023)
The simulation environment and high-fidelity simulators set new challenges for lecturers. The positive impact of simulation training on the development of studentsâ knowledge and skills has been confirmed, but little research has been conducted on the factors that are key elements to performance. The aim of the study was to assess the impact of simulation training on the acquisition of studentsâ skills and learning outcomes in pre-clinical practice and in a practical working environment. The current study is empirical and descriptive, using qualitative and quantitative methods. The study was carried out in 2017â2021. The sample consisted of second- year students and faculty members with simulation teaching experience. Semi-structured interviews were conducted with 5 university lecturers and 16 students. The Educational Practices Questionnaire (78 students) (National League for Nursing 2005) and the Creighton Competency Evaluation Instrument (83 students) (Creighton University 2014) were used and 138 studentsâ practice documentation was assessed. The interviews and documents were analysed using a qualitative content analysis method and the quantitative data were analysed by the method of descriptive statistics. The overall impact assessment of simulation training was visualized by Kirkpatrickâs Four-Level Training Evaluation Model (Kirkpatrick Partners 2017). Simulation training improves the ability to establish links, consolidate knowledge and helps to cope with stressful clinical situations. Negative aspects were video criticism as part of the teaching method, lack of clarity for learning outcomes, limited individual feedback and distortion of reality in the clinical setting. The effectiveness of simulation training is influenced by the teaching staffâs competence and the studentsâ prior experience in the clinical setting.